2008
DOI: 10.1111/j.1600-9657.2008.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental trauma in an Australian rural centre

Abstract: The maxillary central incisors were the most commonly injured teeth in both the primary and permanent dentitions. Uncomplicated crown fractures were the most common injury followed by luxations and subluxations. No significant differences in frequency were reported for the different days of the week, the different months or seasons of the year. Only one-third of the patients presented for dental treatment within 24 h of the injury while the remainder delayed seeking treatment for varying times up to 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
99
3
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 24 publications
(93 reference statements)
30
99
3
21
Order By: Relevance
“…Our results also confi rmed the fi ndings of other studies 43,44 that the majority of aff ected patients were treated more than 24 hours after accidents. However, the results on the time elapsed between sustaining the injury and receiving dental treatment for primary teeth were higher than in other studies due to incorrect routines by general practitioners in Zagreb.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also confi rmed the fi ndings of other studies 43,44 that the majority of aff ected patients were treated more than 24 hours after accidents. However, the results on the time elapsed between sustaining the injury and receiving dental treatment for primary teeth were higher than in other studies due to incorrect routines by general practitioners in Zagreb.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the etiology and site of occurrence, falls and home were the most cited (81.3% and 77.5%, respectively), which is consistent with the literature (3,5,8). A possible explanation is the fact that children in the evaluated age group spend most of their time at home.…”
Section: Discussionsupporting
confidence: 86%
“…This event is usually sudden, unexpected and accidental and often requires dental care (8). In general, laypersons are unaware of the risks of trauma and possible harm to the primary and permanent dentition or what can be done to avoid such situations (7).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings, many studies showed that males are more prone than females to dento-alveolar trauma (10,11). However, we found no statistically significant difference in soft tissue injuries according to gender in common with other studies (12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 78%
“…As reported in the literature, the high incidence of such injuries may be due to the protrusive structure of the maxilla (4,11,13,21,23). In the present study, soft tissue injuries were most frequently found in the maxilla as previous studies.…”
Section: Discussionsupporting
confidence: 77%